The scent of life: Foreword from the Editors - Campos, Luiz Alexandre; Schwertner, Cristiano Feldens (Zootaxa, 2021)
This special issue of Zootaxa is published in honor of Dr. Jocélia Grazia (Fig. 1) from the Universidade Federal do Rio Grande do Sul, Brazil, one of the world’s most respected and influential active taxonomists in Heteroptera. Though she retired from her long-time position as a Full Professor, away from undergraduate classes and administrative duties, Jocélia is still an active researcher and passionate about studying true bugs. An intense conviction she passes to her many students and becomes evident in her publications. If there is one word to define Jocélia Grazia, it is energy. Even the most novice and inexperienced student perceives the enthusiasm and dedication Jocélia faces from the small bureaucratic problems through the most challenging scientific questions.